PENERAPAN MEDIA MAZE DAN POHON ANGKA TERHADAP KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN DI TK MADANI LUBUK PAKAM T.A 2022-2023 - Indah Anggraini; Darajat Rangkuti (Jurnal Educhild : Pendidikan dan Sosial, 2023)
Based on observations at MADANI Lubuk Pakam Kindergarten, it can be said that children's cognitive abilities are still underdeveloped. The purpose of this study was to determine which is more effective the use of maze media than the use of number tree media on cognitive abilities of children aged 5-6 years at MADANI Lubuk Pakam Kindergarten T.A 2022-2023. This research is a type of quantitative research with a research design using a quasi-experiment with a control group pre-test posttest approach. Parallel design is used to compare between two independent groups (group comparison), namely the control group and the experimental group. The population to recognize children's abilities is 40 children from 4 indicators. And the research sample is group B students of MADANI Lubuk Pakam Kindergarten, namely the nature center class of 20 children and the art center class of 20 children. The average value before using the maze media is 7.05, and the number tree media is 7, the average value after using the maze media is 14.35 and the number tree media is 12.45. The data analysis technique uses statistical tests, namely normality test, homogeneity test, and also hypothesis testing using the T test. According to the results of the research obtained Thitung = 1.91 then compared to the price of Ttabel at dk = (n1 + n2) - 2 = (20 + 20) - 2 = 38 from a significant level of 5% (α = 0.05) found in the distribution list Ttabel is 1.68. So by comparing between Thitung and Ttabel, it is obtained that Thitung> Ttabel, then H0 is rejected and Ha is accepted, namely 1.91> 1.68. With the price of Thitung> Ttabel, this indicates that there is a difference in the score of the post-test results between the maze media and the number tree media. So it can be concluded that children's cognitive abilities using maze media are more effective than using number tree media in children aged 5-6 years at MADANI Lubuk Pakam Kindergarten.